PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH EVALUASI HASIL BELAJAR - Revita Yuni (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
The research was background by student’s of result of  students evaluation subjects at Department of Economic Education, University Of Medan still low. In this case, the lecture is still using lecture and discussion methods in teaching and learning. In the discussion of the method is still often a child is not want to try (passive) in solving problems (questions) given lecturers, just waiting for a response from his friends only. One of the way that can use to problem solve, it’s cooperative learning of jigsaw type. Purpose of this study evaluation subjects student learning outcomes using cooperative learning of jigsaw type better than discussion method in semester V at Department of Economic Education, University Of Medan. The types of experimental research is the subject of purposive sample. The data used was obtained by t analysis. Based on data analysis, SPSS 21, with a probability value of 0.001. Thus, we can conclude the results of the evaluation subjects study of students taught with cooperative learning  outcomes students who were taught by using cooperative learning of jigsaw type had higher outcomes than students who were taught by using discussion method in semester V at Department of Economic Education, University Of Medan, the trust level is 95%.Keywords: Cooperative learning, Jigsaw-type Model, the results of the study